Effect of antimicrobial administration on fecal microbiota of critically ill dogs: dynamics of antimicrobial resistance over time - Julie Menard; Robert Goggs; Patrick Mitchell; Yufan Yang; Sarah Robbins; Rebecca J. Franklin-Guild; Anil J. Thachil; Craig Altier; Renee Anderson; Gregory G. Putzel; Holly McQueary; Laura B. Goodman (Animal Microbiome, 2022)
Abstract Background Multidrug resistance in companion animals poses significant risks to animal and human health. Prolonged antimicrobial drug (AMD) treatment in animals is a potential source of selection pressure for antimicrobial resistance (AMR) including in the gastrointestinal microbiota. We performed a prospective study of dogs treated for septic peritonitis, pyometra, or bacterial pneumonia and collected repeated fecal samples over 60 days. Bacterial cultures and direct molecular analyses of fecal samples were performed including targeted resistance gene profiling. Results Resistant Escherichia coli increased after 1 week of treatment (D1:21.4% vs. D7:67.9% P < 0.001) and returned to baseline proportions by D60 (D7:67.9% vs D60:42.9%, P = 0.04). Dogs with septic peritonitis were hospitalized significantly longer than those with pneumonia or pyometra. Based on genetic analysis, Simpson’s diversity index significantly decreased after 1 week of treatment (D1 to D7, P = 0.008), followed by a gradual increase to day 60 (D1 and D60, P = 0.4). Detection of CTX-M was associated with phenotypic resistance to third-generation cephalosporins in E. coli (OR 12.1, 3.3–68.0, P < 0.001). Lincosamide and macrolide-resistance genes were more frequently recovered on days 14 and 28 compared to day 1 (P = 0.002 and P = 0.004 respectively). Conclusion AMR was associated with prescribed drugs but also developed against AMDs not administered during the study. Companion animals may be reservoirs of zoonotic multidrug resistant pathogens, suggesting that veterinary AMD stewardship and surveillance efforts should be prioritized. Graphical abstract